Escuela de padres : un modelo centrado en valores. (1999)
This article is a study of an alternative model of Parents? School.The background records, historical and social elements and some investigations from different Latin- American countries and from Colombia were examined to identify the schemes of work. Finally, the proposed model appears methodologically supported on participant research conceiving the family from the systems theory and the contents of the school from values development and life quality.